Perdidas en el rendimiento y la calidad de la yuca (Manihot esculenta Crantz) causadas por coquito (Cyperus rotundus L.) - Leihner, D.E.; López M., J. (1980)
The type and magnitude of losses in cassava caused by Cyperus rotundus were determined. Two field expt. were conducted at Instituto Colombiano Agropecuario-Caribia exptl. station, Magdalena (Colombia) at 35 m.a.s.l. The location has an annual mean temp. of 280 degrees Celsius, mean annual precipitation is 1350 mm, and the soil is a sandy loam with intermediate fertility. Cassava cv. M Col 22 was planted on ridges at 1 x 1 m in plots with heavy C. rotundus infestation and free of purple nutsedge. Loss in fresh tuber yield caused by C rotundus was 17 percent. This significant reduction of yield was mainly due to competition for water and nutrients whereas competition for light appeared to be minimal. Yield reduction was a consequence of a reduction in the no. of thickened roots while root size was not affected. There was also a small but nonsignificant reduction in the starch concn. of the roots. The relatively moderate yield and quality reduction in cassava as compared with other crops is probably explained by the small influence that C. rotundus has on the growth of cassava roots, a long vegetative cycle, and the absence of a critical period foryield formation. Economic implications of these findings are discussed; in cassava, good agronomic practices and cultural control methods should have prevalence over repeated applications of costly chemicals. (AS)